Digital Leadership Model in Private Universities in Palembang: Empirical Analysis and Proposed Strategic Transformation Model - Indriani Indriani; Yunita Hasrina; Tedy Setiawan Saputra; Nozylianti Nozylianti (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study analyzes the implementation of digital leadership in private universities in Palembang and develops a comprehensive digital leadership model that supports strategic transformation and sustainable innovation in higher education institutions. Design/methodology/approach – This research employs a qualitative exploratory approach involving leaders from five private universities in Palembang. Data were collected through in-depth interviews and analyzed using NVivo 15 software. The analysis utilized Word Cloud, Treemap, and Hierarchy Chart visualizations to identify key themes, leadership patterns, and relationships among digital leadership dimensions. Findings/Results – The findings indicate that current digital leadership practices are predominantly operational in nature and remain fragmented across seven key dimensions: digital vision, inclusive leadership, data-driven decision making, digital sustainability, empowerment and collaboration, technology adoption, and sustainable innovation. Based on these findings, a comprehensive digital leadership model is proposed, integrating both internal and external factors while emphasizing long-term digital strategies, stakeholder collaboration, institutional adaptability, and global competitiveness. Originality/Value – This study contributes to the literature on higher education leadership by proposing a contextual digital leadership model tailored to private universities in Indonesia. The research also demonstrates the usefulness of NVivo-based qualitative visualization techniques in leadership studies and provides practical guidance for university leaders seeking to move from operational digitization toward strategic digital transformation and sustainable institutional development.